Spatial constraints on visual-tactile cross-modal distractor congruency effects. - Spence, C; Pavani, F; Driver, J (2004)
Across three experiments, participants made speeded elevation discrimination responses to vibrotactile targets presented to the thumb (held in a lower position) or the index finger (upper position) of either hand, while simultaneously trying to ignore visual distractors presented independently from either the same or a different elevation. Performance on the vibrotactile elevation discrimination task was slower and less accurate when the visual distractor was incongruent with the elevation of the vibrotactile target (e.g., a lower light during the presentation of an upper vibrotactile target to the index finger) than when they were congruent, showing that people cannot completely ignore vision when selectively attending to vibrotactile information. We investigated the attentional, temporal, and spatial modulation of these cross-modal congruency effects by manipulating the direction of endogenous tactile spatial attention, the stimulus onset asynchrony between target and distractor, and the spatial separation between the vibrotactile target, any visual distractors, and the participant's two hands within and across hemifields. Our results provide new insights into the spatiotemporal modulation of cross-modal congruency effects and highlight the utility of this paradigm for investigating the contributions of visual, tactile, and proprioceptive inputs to the multisensory representation of peripersonal space.